Sosialisasi Tentang Manusia Sebagai Homo Digital Pada Siswa Kelas XII SMA Ikarasi Melalui Pengenalan Aplikasi Corel Draw - Rondo, Donsianus; Weru Tana, Sandi; X. Subun, Fransiskus; Coryunitha Panis, Isabel (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
The result of community service on the socialization of Humans as Homo Digital to class XII students of Ikarasi High School through the introduction of the Corel Draw application is an increase in students' technological skills in graphic design. This activity involves training and practice in using the Corel Draw application to create creative and attractive graphic designs. In this activity, students learn about how to use the Corel Draw application to create quality graphic designs. They also learn about techniques and strategies in creating attractive graphic designs as well as how to use digital technology wisely and effectively. The result of this activity is students who have technological skills in creating graphic designs, as well as understanding how digital technology can improve the quality of their work. In addition, this activity also increases students' awareness of the risks and potential negative impacts of unwise use of digital technology, such as addiction, social isolation, and mental health disorders. In conclusion, the community service activity on the socialization of "Humans as Digital Homo" to class XII students of Ikarasi High School through the introduction of Corel Draw application is an effective way to improve students' technological skills in graphic design, as well as increase their awareness about the wise and effective use of digital technology. This can provide benefits for students in improving the quality of their work and preparing them to live and work in the digital era.